Implementasi Abreviasi dalam Tajuk Akun Youtube Najwa Shihab - Ermira Nilansari Putri; Atiqa Sabardila (Institut Agama Islam Negeri Curup, 2021)
This study aims to show the suitability of the abbreviation used on YouTube social media. It provided a description of the problems that arise regarding the emergence of various forms of abbreviations, as well as analyzed the meaning contained in the abbreviations in Youtube account header.Â It employed a qualitative descriptive approach (in the form of a content analysis process and data of a collection of tangible words). The technique of providing data utilizes the free-of-conversation listening technique. The approach used in this study was a qualitative approach with Miles Huberman's analytical model. The data analysis model used was the flow model of analysis. The sources of the data the title on Najwa Shihab's Youtube channel. This study analyzed twenty two data that utilize abbreviations on them. It contained eight data in the abbreviation domain. In the realm of fragments, seven data have been found. The acronym domain in this study consisted of eight data. Then, in the contraction and letter symbols, there was one datum. With regard to the majority of the most frequent occurrences of each type of abbreviation in the header of Najwa Shihab's youtube account wereÂ 32% abbreviations, 28% fragments, 32% acronyms, 4% contractions, and 4% letter symbols.